Competition in an alfalfa-tall fescue mixture under Mediterranean conditions - Lazaridou M.; Kostopoulou P.; Karatassiou M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The focus of the current study was to evaluate the competitive ability of two forage species (alfalfa- Medicago sativa L., and tall fescue- Festuca arundinacea Schreb.) grown in dry and disturbed soils either in mixture (1:1) or in monocultures, for capture of sunlight. Two levels of water regimes were used: a) frequent irrigation by sprinkler to the point of field capacity and b) no irrigation (drought) conditions. The plants were cut in about 20 day time intervals, at height of 7 cm above soil surface. Measurements of the leaf area and the dry weight of leaves and stems were conducted during two successive growing seasons, and the leaf area ratio (LAR), the leaf weight ratio (LWR) and the leaf area index (LAI) were calculated. Our results showed that: mixture reduced significantly LAR and LAI of alfalfa only under irrigation, while these indices were unaffected in tall fescue; under both water regimes, the alfalfa LAI was higher to the corresponding tall fescue LAI; drought and mixing did not affect LWR, which remained higher in tall fescue compared to alfalfa during the season of experimentation. We conclude a lower competition ability of alfalfa to tall fescue under irrigation and therefore lower productivity.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)